PENDAMPINGAN UMKM KOPI SEMBALUN MENUJU PRODUK UNGGULAN EKSPOR MELALUI PENINGKATAN KUALITAS DAN STRATEGI PEMASARAN - Trimulyanto, Athoriq; Ardiansyah, Muhammad; Afrida, Merisa; putri, Nadila Ayu; Rhamdhani, Noval; Kurniawan, Lalu Bisma Haris; Agustin, Pradita Ayu; Wardani, Suci; Fatimah, Sukma; Jayadi, Imran; Sarjan, M. (Jurnal Wicara, 2025)
Sembalun coffee has a distinctive flavor influenced by the geographical and climatic conditions of Mount Rinjani, making it a potential export commodity. However, limited technical capacity of SMEs in meeting quality standards, certification, packaging, and the low use of digital marketing remain key challenges. This program aimed to assist Sembalun coffee SMEs in improving product quality and expanding international market access. The methods included field observations, interviews, focus group discussions, Workshops, field practices (seedling, planting, harvesting), and halal certification assistance. The results showed an increase in partners’ knowledge of quality standards, strengthened skills in post-harvest processes, and improved awareness of the importance of digital marketing. Partners also successfully obtained halal certification, which enhanced product competitiveness in both national and international markets, and began adopting digital marketing strategies to broaden sales reach. In conclusion, this mentoring program significantly contributed to preparing Sembalun coffee as an export-oriented product while improving local economic sustainability.